2017
DOI: 10.1186/s13756-017-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of surface coatings containing silver ions in bacterial decontamination in a recovery unit

Abstract: BackgroundHAIs remain a frequent complication for hospitalised patients and pose a challenge that must be tackled by our health systems.MethodsQuasi-experimental study. In order to determine the antimicrobial effectiveness of surface coating agents containing silver ions (BactiBlock®) the degree of contamination of several surfaces in two ICU wards was compared.The association between application of Bactiblock® and surface contamination was analysed using a relative risk (RR). Multivariate logistic regressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…It was observed that applying the disinfectant significantly decreased the bacterial and viral contamination on the surface. Tamimi et al [ 10 ] and Orti-Lucas and Munoz-Miguel [ 11 ] also indicated that microbial contamination can be reduced via the surface coating of equipment with various substances, which is in agreement with our results.…”
supporting
confidence: 93%
“…It was observed that applying the disinfectant significantly decreased the bacterial and viral contamination on the surface. Tamimi et al [ 10 ] and Orti-Lucas and Munoz-Miguel [ 11 ] also indicated that microbial contamination can be reduced via the surface coating of equipment with various substances, which is in agreement with our results.…”
supporting
confidence: 93%
“…Contaminated surfaces in public places, such as hospitals, parks, public transportation and schools, are a well-recognized common source for outbreaks of infection [ 46 , 47 ]. Some studies have shown the potential of nano-based surface coatings for prevention of infections [ 48 50 ]. Also, the protection of healthcare workers is very important in a viral outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium hypochlorite disinfection, which comprised any disinfection method specified as bleach or sodium hypochlorite, was identified in 19% of studies [20,44,60 For surface interventions, we found that copper surfaces were in 9% of studies [90,132,152,154,[167][168][169][170][171][172][173][174][175][176][177][178][179]. Other non-copper surface applications or coatings comprised 8% of studies [87,102,[180][181][182][183][184][185][186][187][188][189][190][191][192]. Other non-copper surfaces included coatings incorporating metals such as titanium oxide and silver ions as well as other coatings comprised of polymers, isopropyl alcohol and organofunctional silane, organosilane products, silicon nano-coating inorganic metal and organic quaternary ammonium, silicone quaternary amine, quaternary ammonium silyl oxide, and titanyl oxide moieties.…”
Section: Disinfection Typementioning
confidence: 99%